Four new species and new records for the spider genus Synotaxus Simon, 1895 (Araneae: Synotaxidae) from Brazil - Santos, Adalberto J.; Rheims, Cristina A. (Zootaxa, 2005)
Four new species of Synotaxus Simon are described and illustrated based on material from northern and northeastern Brazil: S. brescoviti n. sp., S. bonaldoi n. sp., S. siolii n. sp. and S. itabaiana n. sp. New records are presented for S. longicaudatus (Keyserling), S. monoceros (Caporiacco) and S. waiwai Agnarsson. A map with all species records included is provided.